Halogenated Anesthetics Determination in Urine by SPME/GC/MS and Urine Levels Relationship Evaluation with Surgical Theatres Contamination - Serena Indelicato; David Bongiorno; Sergio Indelicato; Leopoldo Ceraulo; Ernesto Tranchina; Giuseppe Avellone; Concetta Arcadipane; Filippo Giambartino (Journal of Analytical Methods in Chemistry)
In this work, a new sensitive analytical method has been developed and evaluated for the determination of the most commonly used gaseous anesthetics, desflurane, sevoflurane, and this latter’s hepatic metabolite hexafluoroisopropanol (HFIP) in the urine. In addition, an evaluation of anesthetics exposition on the urine levels of a small population of surgical operators has been performed and results are briefly discussed.